2014
DOI: 10.1111/ajt.12847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HCV, HIV and Coinfection in Kidney Transplant Recipients: Mate Kidney Analyses

Abstract: Reports of kidney transplantation (KTX) in recipients with hepatitis C virus (HCVþ), human immunodeficiency virus (HIVþ) or coinfection often do not provide adequate adjustment for donor risk factors. We evaluated paired deceased-donor kidneys (derived from the same donor transplanted to different recipients) in which one kidney was transplanted into a patient with viral infection (HCVþ, n ¼ 1700; HIVþ, n ¼ 243) and the other transplanted into a recipient without infection (HCVÀ n ¼ 1700; HIVÀ n ¼ 243) using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 42 publications
(67 reference statements)
1
43
1
1
Order By: Relevance
“…Mate kidney analyses using SRTR database from 2000 to 2013 showed similar long term outcomes of kidney transplantation in HIV positive patients relative to noninfected recipients. HIV and HCV coinfected patients had inferior outcomes in this analysis [20] . European transplant centers have similar experience to that in the United States.…”
Section: Nashar K Et Al Kidney Transplant In Hiv Infected Patientsmentioning
confidence: 61%
See 2 more Smart Citations
“…Mate kidney analyses using SRTR database from 2000 to 2013 showed similar long term outcomes of kidney transplantation in HIV positive patients relative to noninfected recipients. HIV and HCV coinfected patients had inferior outcomes in this analysis [20] . European transplant centers have similar experience to that in the United States.…”
Section: Nashar K Et Al Kidney Transplant In Hiv Infected Patientsmentioning
confidence: 61%
“…As mentioned, outcomes were inferior with kidney transplantation in patients coinfected with HIV and HCV when compared to HIV monoinfected transplant recipients [19,20] . Factors contributing to this may include HCV infection related increased risk for the development of post-transplant diabetes mellitus, liver damage, cardiovascular disease and infections.…”
Section: Patients Coinfected With Hiv and Hcvmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite the proven immunoprotective effect of simultaneously transplanted liver, the intestinal allograft experienced significant histopathologic damage (11,18). Dysregulation of the innate immune response due to HIV infection may also have contributed to the observed higher risk of destructive alloimmunity as observed with solid organs (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). It is also possible that ischemic injury upregulated the allogeneic response.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Hepatitis C virus infection has negative effects on both patient and graft survival. 2,4,5 A meta-analysis demonstrated that the presence of HCV antibodies was an independent and significant risk factor for death (risk ratio = 1.79; 95% confidence interval [CI], 1.57-2.03; P = .042) and graft failure (risk ratio = 1.56; 95% CI, 1.35-1.80; P = .019) after kidney transplant. 6 The lower survival was related to the posttransplant progression of liver disease induced by the use of immunosuppressive regimens 7,8 and increased risk for development of extrahepatic complications of HCV infection, including posttransplant de novo or recurrent glomerular disease and new-onset diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%